2013
DOI: 10.1161/circulationaha.113.002480
|View full text |Cite
|
Sign up to set email alerts
|

Novel Role of Silent Information Regulator 1 in Myocardial Ischemia

Abstract: T he incidence of cardiovascular diseases is increasing at an alarming rate throughout the world. According to the World Health Report 2010, cardiovascular disease accounts for 17.1 million global deaths per year, or 29% of total deaths worldwide. It is predicted that this number will increase to 23.6 million by 2030. Myocardial ischemia, which is reported to induce irreversible damage to the myocardium, causes a number of cardiovascular diseases, such as myocardial infarction, myocardial hypertrophy, atherosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 87 publications
0
57
0
Order By: Relevance
“…SirT1 has been reported to be involved in a variety of cellular functions. 35 Recent data also suggests that SirT1 is a critical mediator in regulation of various development genes during stem cell differentiation 36 and has an important role in various cellular differentiations, including endothelial progenitor cells, 37 hematopoietic cells 38 and osteoblasts. 39 Traditionally, SirT1 has mainly been linked to gene repression; 40 however, accumulating evidence also strongly suggests that SirT1 can act both positively and negatively to control gene expression by recruiting a different set of coactivators and corepressors 41 or via a transcriptional mechanism.…”
Section: S Ir T 1 a C T A 2 T A G Lnmentioning
confidence: 99%
“…SirT1 has been reported to be involved in a variety of cellular functions. 35 Recent data also suggests that SirT1 is a critical mediator in regulation of various development genes during stem cell differentiation 36 and has an important role in various cellular differentiations, including endothelial progenitor cells, 37 hematopoietic cells 38 and osteoblasts. 39 Traditionally, SirT1 has mainly been linked to gene repression; 40 however, accumulating evidence also strongly suggests that SirT1 can act both positively and negatively to control gene expression by recruiting a different set of coactivators and corepressors 41 or via a transcriptional mechanism.…”
Section: S Ir T 1 a C T A 2 T A G Lnmentioning
confidence: 99%
“…Recent biophysical data indicate that resveratrol interacts with and modulates SIRT1 activity via an allosteric mechanism (Cencioni et al 2015;Hubbard et al 2013;Sinclair and Guarente 2014); these findings interestingly indicate that micromolar levels of resveratrol are sufficient to exert vasculoprotective effects through SIRT1 action (Csiszar et al 2009;Della-Morte et al 2009;Pacholec et al 2010;Ungvari et al 2007;Yang et al 2013). However, some data have suggested that resveratrol seems more likely act through a complex indirect mechanism dependent on the inhibition of phosphodiesterases (PDE) paralleled by AMPK activation (Beher et al 2009;Cencioni et al 2015;Park et al 2012;Yang et al 2013). Furthermore, resveratrol has been further shown to protect coronary endothelial cells against oxidative stress: in fact, it may stimulate in a dose-dependent manner SIRT1 deacetylase activity by increasing its binding affinity to both the acetylated substrate and NAD + (Howitz et al 2003).…”
Section: The Sirtuin Familymentioning
confidence: 97%
“…SIRT1 has been confirmed also as a key factor in myocardial hypertrophy; low to moderate SIRT1 heart expression (2.5-to 7.5-fold over endogenous levels) was found to be protective against age-dependent cardiac hypertrophy, apoptosis, and consequent left ventricular dysfunction, whereas SIRT1 overexpression (12.5-fold) induced dilatation, hypertrophy, and cardiac failure (Alcendor et al 2007;Ma et al 2010;Yang et al 2013). SIRT1 also provides protection against apoptosis playing an essential role in mediating the survival of cardiac myocytes under stress in vitro (Alcendor et al 2004;Alcendor et al 2007;Wang et al 2007).…”
Section: The Sirtuin Familymentioning
confidence: 99%
See 2 more Smart Citations